Analisis Kontribusi Sektor Umkm Terhadap Pendapatan Asli Daerah Kota Semarang - Alifia Martdanesya Putri; Cintya Sofwatulmala; Mubayyinah Mubayyinah; Naela Rana Hanifah; Ameylia Zahra Subagyo (Universitas Pakuan, 2026)
ANALYSIS OF THE CONTRIBUTION OF THE MSME SECTOR TO REGIONAL OWN-SOURCE REVENUE (PAD) OF SEMARANG CITY Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the economy, contributing significantly to job creation and national economic stability. This study aims to analyze and empirically test the effect of growth in the number of MSMEs on the Regional Gross Domestic Product (GDP) in Semarang City. The research approach adopted is quantitative, using a simple linear regression analysis method assisted by the SPSS program. Secondary data on periodic reports on registered MSMEs and PAD realization were collected through documentation from relevant institutions, covering a time-series sample from the past eight years (2017 to 2024). The correlation analysis results demonstrate a very strong, positive relationship between the number of MSMEs and PAD, with a Pearson correlation coefficient of 0.97 (r = 0.97) and a significance level of 0.000 (p < 0.05). Simple linear regression testing yielded the model equation Y = 1,087,091,757,115.167 + 55,635,499.07X, which implies that each additional registered MSME unit is predicted to increase the PAD of Semarang City by IDR 55,635,499.07. Furthermore, the coefficient of determination (R²) reached 0.941, indicating that variations in the number of MSMEs can explain 94.1% of changes in PAD, while the remaining 5.9% is influenced by other factors outside the model. This study concludes that the quantity of MSME actors plays a strategic role in supporting regional fiscal independence. It is recommended that local governments continue to reinforce supporting regulations through business licensing formalization, digitalization, and expanding financing access to maximize the absorption of potential local taxes and retributions.